Exploitation Histories of Pangolins and Endemic Pheasants on Hainan Island, China: Baselines and Shifting Social Norms - Wang, Yifu; Leader-Williams, Nigel; Turvey, Samuel T. (Frontiers in Ecology and Evolution, 2021)
Overexploitation is a critical threat to the survival of many species. The global demand for wildlife products has attracted considerable research attention, but regional species exploitation histories are more rarely investigated. We interviewed 169 villagers living around seven terrestrial nature reserves on Hainan Island, China, with the aim of reconstructing historical patterns of hunting and consumption of local wildlife, including the globally threatened Chinese pangolin (Manis pentadactyla) and Hainan peacock-pheasant (Polyplectron katsumatae), from the mid-20th century onwards. We aimed to better understand the relationship between these past activities and current consumption patterns. Our findings suggest that eating pangolin meat was not a traditional behaviour in Hainan, with past consumption prohibited by local myths about pangolins. In contrast, local consumption of peacock-pheasant meat was a traditional activity. However, later attitudes around hunting pangolins and peacock-pheasants in Hainan were influenced by pro-hunting policies and a state-run wildlife trade from the 1960s to the 1980s. These new social norms still shape the daily lifestyles and perceptions of local people towards wildlife consumption in Hainan today. Due to these specific historical patterns of wildlife consumption, local-adapted interventions such as promoting substitute meat choices and alternative livelihoods might be effective at tackling local habits of consuming wild meat. Our study highlights the importance of understanding the local historical contexts of wildlife use for designing appropriate conservation strategies.